KEEFEKTIFAN MODEL PEMBELAJARAN ROLE PLAYING PADA MATA KULIAH RETORIKA - dan Leli Triana, Khusnul Khotimah (Sasando, 2020)
His study intends to describe the ability of students in rhetoric subjects in the subject of "Application of Rhetoric" by using a role playing model and to describe the effectiveness of this role playing model. This study uses experimental research methods. Experimental research itself is a study that is intended to determine whether there is a consequence of something imposed on the subject under investigation. Role playing is more effective in learning rhetoric compared to not using role playing models in learning rhetoric in class IV Indonesian Language and Literature Education Study Programs, Pancasakti University, Tegal. This is evidenced by the results of t count 15.26> t table 1.67 in the calculation using the non-independent t test. Rhetoric learning using a role playing model is more effective than those that do not use role playing in its learning. This result is evidenced by the mean value of the experimental class 83.40 which is greater than the control class which is only 77.92. In learning rhetoric using role playing models, students are more active and creative in practice and understand rhetoric, and students' insights are more related to deepening character in rhetoric.